Pengaruh Lingkungan Kerja, Pelatihan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan - Puspitasari, Devy Mawarnie; Agustini, Kamelia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to determine the influence of the work environment, work training, and work motivation on employee performance at Hotel Santika Cikarang. The population in this study were all employees of Hotel Santika Cikarang. Determination of sample using saturated sample techniques. The data collection method uses a survey method with the research instrument being a questionnaire. The data analysis method used in this research is the Structural Equation Model (SEM) – Partial Least Square (PLS) with the Smart-PLS analysis tool. The results of this research show that the work environment, work training and work motivation have a positive and significant effect on the performance of Hotel Santika Cikarang employees.